Solvent and melt based extrusion 3D printing of polycaprolactone bioactive glass composite for tissue engineering - Kolan, Krishna C.R. (2018)
Bioactive glasses are widely used in tissue engineering because of their several unique and interesting characteristics including promoting angiogenesis. In 3D bioprinting, bioactive glasses are added to bio-ink in limited weight percentages to promote bioactivity. In this study, we investigate two different approaches, solvent-based and melt-based extrusion 3D printing, to fabricate scaffolds using a bioactive glass contained polymer composite suitable for bioprinting applications. Highly angiogenic and bioactive borate glass (13-93B3) is added to polycaprolactone (PCL) in 50 wt.% to prepare the polymer-glass composite. The scaffolds fabricated using the two approaches are studied for their mechanical properties, degradation, and bioactivity. The scaffold stiffness and yield strength increased after the addition of borate glass irrespective of the fabrication approach. Scaffolds were soaked in minimum essential medium for up to four weeks to study weight loss and bioactivity. The weight loss results indicated a faster borate glass dissolution in scaffolds made using solvent-based 3D printing whereas an apatite-like layer was formed on scaffolds fabricated with both approaches.